IMPLEMENTASI PERDA NO. 13 TAHUN 2004 TENTANG RENCANA DETAIL TATA RUANG KOTA (RDTRK), KOTAMADYA DAERAH TINGKAT II KOTAMADYA SEMARANG BWK VIII (KECAMATAN GUNUNG PATI) - Widyawati, Anis (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Analysis of the level of vertical synchronization Regional Regulation No. 13/2004 witu the Law No. 32 of 2009 needs to be done with regard to the mechanism of licensing and environmental management authority. To overcome the barriers in terms of supervision, counseling needs to be done at neighborhood related new building is right. The Regional Regulation does not give a detailed explanation about the administrative sanctions so that in practice sanctions are rarely performed. The government needs to encourage responsible business and/or activity to conduct an en-vironmental audit. As implementers at district level Gunungpati, the government should also establish environmental auditor district.Key words: licensing, controling, criminal sanctions, environmental auditing